The Potential of Butterfly Pea Flower Methanol Extract as an Antioxidant by in Silico - Tiana Fitrilia; M. Fakih Kurniawan; Febryana Rahayu Kurniawati; Tirta Setiawan (Indonesian Journal of Applied Research (IJAR), 2020)
Abstract: Butterfly pea flower (Clitoria ternatea L.) is a flowering plant from the Fabecea family that can grow vines. Butterfly pea flower are known to have chemical components that can act as antioxidants. This study aims to predict the potential of active compounds from methanol extract of butterfly pea flower in inhibiting reactive oxygen species (ROS) based on bond affinity (∆G), the value of Root Mean Square Deviation (RMSD) and their interactions. The method used was a computational method with in silico technique. The software used was Autodock Vina with visualization using the Biovia Discovery Studio Visualizer 2020. The enzyme receptor was NADPH Oxidase (NOX) obtained from Protein Data Bank and the test ligands were a chemical compound from methanol extract of butterfly pea flower. The results of the in silico study showed that the NO had a innate ligand, namely the GTP ligand which has a ∆G value of -7.3 kcal/mol, an RMSD value of 3.1111 Å and the interaction with the receptor that involves the presence of hydrogen bonds. Based on the results of the analysis of 11 test ligands, the chemical component of caffeine was predicted to have the most potential in inhibiting ROS compounds with a value of ∆G -5.4, RMSD value of 1.328 Å and had the same amino acid residue in hydrogen bonding, namely ASP118, and GLY15. The test ligand had the ability to inhibit ROS compounds with a lower level of stability than the innate ligand. Keywords: antioxidant; butterfly pea flower; in silico; NADPH oxidase, ROS